Smart city planning focused on the US cities in need of policing innovations and public health safety technologies and strategies - Delores Springs (Health Economics and Management Review)
The issue of firearm-related injuries, deaths and crime in the United States is of particular relevance. Every year, about 32,000 lives are lost as a result of firearm-related incidents, including self-inflicted injuries. Other 74,000 people suffer non-fatal gunshot wounds. Addressing this multi-faceted problem is possible through a comprehensive and integrated approach that encompasses public health initiatives, law enforcement efforts, and security measures. In the context of solving this problem, the concepts of “community-oriented policing”, “problem-oriented policing”, “broken windows theory”, “smart city social sustainability initiative” (multi-system improvement and meeting the needs of marginalised residents), “feedback methodology”, etc. are thoroughly considered. The author proposes the strategic deployment of mini-police stations in areas with a high crime rate as proper centres of police visibility and a deterrent to criminals. To realise this task, it is necessary to integrate the latest approaches to Smart Urban Development with innovative urban planning technologies that would increase the influence of law enforcement agencies in the process of protecting public health and safety in cities. In particular, the article proposes the following for implementation: identifying crime hotspots by means of advanced geographic information systems, applying machine learning algorithms to predict future crime trends, using advanced real-time surveillance technologies and firearms detection systems, applying geospatial analysis to optimise patrol routes, dynamically adjusting patrol routes depending on real-time data analytics, deploying mobile command centres. As a result, law enforcement agencies can effectively communicate to potential criminals that their actions will not go unnoticed. They may achieve significant success in improving the overall quality of life of residents in such areas. Also, they will create safer communities, and reduce the number of incidents involving the use of firearms.